Revisiting the effect of U-bends, flow parameters, and feasibility for scale-up on residence time distribution curves for a continuous bioprocessing oscillatory baffled flow reactor - Cox, Rylan; Salonitis, Konstantinos; Rebrov, Evgeny; Impey, Susan A. (American Chemical Society, 2022)
Abstract An oscillatory baffled flow reactor (OBR) has been designed with 60 interbaffled cells. The baffled columns of 40 mm internal diameter together result in a reactor length of 5740 mm. The oscillatory amplitude and frequency were in the range of 2–12 mm and 0.3–2 Hz, respectively. The report investigates the impact of U-bends and the number of reactor sections on axial dispersion for scale-up feasibility. A prediction model using operating parameters has been developed to maximize plug flow conditions using the tanks-in-series (TiS) model. The maximum TiS value was 13.38 in a single column compared to 43.68 in the full reactor at a velocity ratio of 2.27 using oscillatory parameters 8 mm and 0.3 Hz. The mixing efficiency along the reactor was found to decrease after each column at amplitudes <6 mm compared to amplitudes up to 12 mm, where a negligible impact was observed. U-bend geometry had a significant role in the decrease of TiS values.
Keywords: Oscillatory Baffled Flow Reactor; Tanks-in-Series; Velocity Ratio; Scale-Up Feasibility; U-Bends